METHOD OF IMPLEMENTATION OF EMBUNG NGEMPLAK IN TRENGGALEK REGENCY, EAST JAVA: METODE PELAKSANAAN EMBUNG NGEMPLAK DI KABUPATEN TRENGGALEK JAWA TIMUR - HARI PRANOTO; SUNARKO (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Trenggalek Regency still faces challenges in the form of isolated villages around watersheds that have not been fully reached by development results. This condition results in underdeveloped pockets of villages whose main characteristics are the difficulty of accessing clean water. This limitation is due to surface water conditions and regional topography that generally do not allow the construction of large irrigation constructions. At the beginning of the Five-Year Development program (Repelita II), the government launched the Presidential Instruction on Disadvantaged Villages with the aim of improving the living standards of people in disadvantaged villages. This study examines the alternative solution to the problem of clean water supply based on topographic conditions and rainfall in the area, namely through the construction of a reservoir as a means of holding relatively small water. This reservoir functions as a water bath that can be used in the dry season. Given the relatively small scale of the built irrigation buildings, all aspects of the building, from the construction to the economic aspect, cannot be compared to the existence of large irrigation buildings. This research aims to provide practical and economical solutions in providing clean water for disadvantaged villages in Trenggalek Regency.